ANALYZING THE SERVICE QUALITY OF TOYOTA TENDEAN WORKSHOP (CV KOMBOS) USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Ticonuwu, Feradha; Lapian, Joice; Tumiwa, Johan (Universitas Sam Ratulangi, 2017)
ABSTRACT: Service quality is an important factor in customer service. Customers service expectation from past experiences and marketing communications make customer satisfy with the service quality. Car is an important thing that is thought to help facilitate human life. Since the means of transportation is discovered, movement of human life becomes more easy and dynamic. More importantly, the car should be in service at the dealership workshop in order to comfort and stability of the car maintained. CV. Kombos in PT. Hasjrat Abadi Manado Tendean street give service like change oil , tune up , repair body and engine cars , and after sales service monthly regularly.The aim for this study is to analyze the service quality of Toyota Tendean Workshop (CV.Kombos) using Important and Performance Analysis. This research has identified 10 elements of service quality attributes which are: The facilities and tools , the comfortable of waiting room , the quick service , staff able explain about product or damage , staff can provide solution , the quickest workers handle the customer complaints , safety products , customer trust , staff understand customer needs , staff provide simplicity.Â Keywords: Service quality , Importance and Performance Analysis